The canonical correlation between the biological markers of performance and physical fitness in high level judo athletes - Vecchio, F. B. Del; Vecchio, A. H. M. Dell; Gonçalves, Aguinaldo; Franchini, E.; Padovani, Carlos Roberto [UNESP] (My University, 2011)
The objective of this research was to verify the relationship between biological markers of performance of elite judo athletes and performance in different physical fitness tests. Twenty-one judo athletes were involved in the present observational and correlational study. Dermatoglyphic variables and the 2D:4D digit ratio were considered as biological markers, while the physical fitness variables analyzed were body fat, maximal strength, muscular power, the aerobic and anaerobic profile, and performance in specific tests. The statistics involved canonical correlations and a multivariate technique. A high and significant canonical correlation was observed between groups of variables, the first expressed by 1=0.999 (p<0.0001) and the second by 2=0.997 (p<0.001). It appears that, beyond height and body mass, total ridge count, pattern intensity for fingers and 2D:4D had more canonical loading. The physical fitness component of the first canonical variable incorporated, with high intensity were: the sum of skinfold thickness, the bench press onerepetition maximum (1RM), upper and lower body aerobic power. In the second canonical variable, physical fitness was composed of the squat 1RM, suspension time on the bar, the SJFT-index, and mean power during the upper body Wingate test. The data of this investigation showed the interdependence between biological markers of performance and physical fitness in high level judo athletes.
Keywords: Biological markers; Dermatoglyphics; 2d:4d ratio; Physical fitness